The 15:17 to Paris - Eastwood, Clint, 1930-; Sadler, Anthony; Skarlatos, Alek; Stone, Spencer; Fischer, Jenna, 1974-; Greer, Judy, 1975-; Lennon, Thomas, 1970-; Sadler, Anthony (Warner Bros Pictures, 2018)
Three Americans discover a terrorist plot aboard a train while in France.
Based on the book by Anthony Sadler.
Widescreen.
Music, Christian Jacob ; editor, Blu Murray ; director of photography, Tom Stern.
Anthony Sadler, Alek Skarlatos, Spencer Stone, Jenna Fischer, Judy Greer, Thomas Lennon.
MPAA rating: PG-13; for bloody images, violence, some suggestive material, drug references and language.
DVD.
Keywords: Drama films; Biographical films; Thrillers (Motion pictures); Historical films